PWE-289 A regional audit on outcomes of endoscopic mucosal resection for colonic polyp cancer. (22nd June 2015) - Yeung, B; Konanahalli, P
Abstract : Introduction: Since the introduction of national colonic screening, the incidence of detection of colonic polyp cancer has increased significantly. Endoscopic mucosal resection (EMR) is the standard technique for excision of polyps. We aim to assess the outcome of polyp cancer management from a prospectively collected database from our regional centralised pathology department. Method: Our study period was from 01/06/2012—31/07/2013. The census date was 30/01/2015. A prospectively collected database of all polyp cancer patients from the West of Scotland centralised pathology unit was assessed. Management outcome including endoscopic malignant suspicion, resection completeness, recurrence, and subsequent intervention were assessed through electronic patient record. Results: 35 polyp cancer were detected in 33 patients over 13 month period. Median age of diagnosis was 66.5 (Max 80.4 – Min 52.4). The median size was 15 mm ((Max 34 mm Min 3 mm). EMR was attempted in 32 (91%) polyp cancer. 1 (3%) polyp cancer was managed by transanal minimally invasive surgery. 2 (6%) were treated by primary resection surgery. Of the cancers treated by EMR, 30 (94%) were located in the descending, sigmoid colon and rectum. 7 (22%) had complete excision based on pathology. At census date, 1 patient had recurrence and required colectomy. In 25 (78%) patients, completeness of excision could not be assessed. 6 (24%) patients were managed by surveillance endoscopy and none were found to have recurrence. No complication was observed in surveillance group. 19 (76%) patients were managed by colectomy. 14 (74%) had no evidence of residual disease in the specimen. The morbidity rate was 20%; these included: 1 (5%) pneumonia, 2 (10%) wound infection and 1 (5%) dehiscence. 1 (5%) patient with liver cirrhosis died within thirty days of operation. Conclusion: A low number of disease recurrence was observed after EMR. Despite the relatively small size and distal position of most detected polyp cancers, completeness of excision could not be assessed in a high number of cases. This leads to a significant number of unnecessary surgery with associated morbitidy and mortality. An increase in adoption of surveillance endoscopy, endoscopic submucosal dissection and flexible endoscopic multitasking platform may improve the management of this group of patients. Disclosure of interest: None Declared. References: Logan RFA, Patnick J, Nickerson C et al . Outcomes of the Bowel Cancer Screening Programme (BCSP) in England after the first 1 million tests. Gut. 2012;61:1439–1446 Saito Y, Uraoka T, Yamaguchi Y, Hotta K, Sakamoto N, Ikematsu H, Fukuzawa M, Kobayashi N, Nasu J, Michida T, et al . A prospective, multicenter study of 1111 colorectal endoscopic submucosal dissections (with video) Gastrointest Endosc. 2010;72:1217–1225